ANALISA SISTEM JARINGAN PIPA DISTRIBUSI AIR BERSIH KECAMATAN LUBUK DALAM KABUPATEN SIAK (STUDI KASUS: KECAMATAN LUBUK DALAM KABUPATEN SIAK) - Rahmat, Hasbur; Siswanto, Siswanto; Trimaijon, Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The clean water obtained by the people of Kecamatan Lubuk Dalam is still very minimal. This is because the groundwater source located in Lubuk Dalam does not qualify as clean water. So far, the people of Kecamatan Lubuk Dalam utilize watersource from rain water and drilled well. Rainwater that is accommodated by the community is not able to meet the needs of the community during the dry season, while the groundwater source obtained from the well has a poor quality so it is not good for public health. Due to the growing progress of Kecamatan Lubuk Dalam, the Siak regency government is seeking to build a clean water treatment plant deep in order to meet the water needs of the local community. The new will be built in the area of LubukDalam, a source of water obtained from the Sungai Basas, the Siak River in the Koto Gasip area.Keywords:, clean water, distribution, , PDAM , EPANET